A graphene oxide doped silver nanoparticle / silver nanowire based hierarchical transparent conductive film, and a preparation method and application thereof

CN122889485APending Publication Date: 2026-10-09天冀桢材科技(河北)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611232820.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]为此,本发明提供一种基于氧化石墨烯掺杂银纳米颗粒/银纳米线的层级透明导电薄膜及其制备方法和应用,以解决现有技术中由于银纳米线易氧化、氧化石墨烯导电通路易被破坏而导致的薄膜导电性能下降的问题

Benefits of technology

本发明采用银纳米线(AgNWs)作为主要导电材料,聚(3,4-乙烯二氧噻吩):聚(苯乙烯磺酸盐)(PEDOT:PSS)用作导电亲水粘接层,在氧化石墨烯(GO)上原位生长银纳米颗粒(AgNPs),形成银纳米颗粒掺杂氧化石墨烯(GO-AgNPs)构建功能层,制备出一种柔性多功能复合透明导电薄膜(TCFs)。其中,导电亲水粘接层的作用是提高聚对苯二甲酸乙二醇酯(PET)基底表面的亲水性,从而促进银纳米线的均匀沉积。AgNWs的作用是提供电流传输通道,作为导电主体。GO-AgNPs覆盖了银纳米线导电网络中的空隙,不仅增强薄膜的导电性能,还降低了纳米线之间的电阻,并有助于隔绝AgNWs和大气中氧气和水分子的接触,显著提升了其环境稳定性。由于这些优异的性能,采用此类TCFs制造的柔性有机发光二极管(OLED)器件表现出卓越的性能。这些结果表明,通过该方法构建的高性能TCF在柔性电子器件中具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889485A_ABST
    Figure CN122889485A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on graphene oxide doped silver nanoparticles / silver nanowire hierarchical transparent conductive film and its preparation method and application, belong to conductive material field.The film from bottom to top includes substrate layer, conductive hydrophilic adhesive layer, conductive layer and functional layer in turn;Wherein, the material of substrate layer is polyethylene terephthalate, the material of conductive hydrophilic adhesive layer is poly (3, 4-ethylenedioxythiophene) : poly (styrene sulfonate) ;The material of conductive layer is silver nanowire, and the material of functional layer is graphene oxide sheet layer of in-situ growth silver nanoparticles.The gap in silver nanowire conductive network is covered by GO-AgNPs in the application, the conductive performance of film is enhanced, and its environmental stability is significantly improved.The problem of film conductive performance decline caused by silver nanowire easy oxidation and graphene oxide conductive path easy to be damaged in prior art is solved.It has potential for application in the preparation of OLED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive materials technology, specifically to a layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires, its preparation method, and its application. Background Technology

[0002] Flexible transparent conductive films (TCFs) are a type of flexible conductive material that has attracted much attention in recent years. They possess excellent flexibility, light transmittance, and conductivity, making them a key component in modern electronics technology. They are widely used in foldable screens, solar cells, and smart wearable electronic devices, and are important materials for making electronic devices lighter, more flexible, and more intelligent.

[0003] Silver nanowires (AgNWs) can form conductive networks in thin films, a structure that combines high light transmittance with low surface resistance, making them ideal flexible thin-film conductive materials. However, their susceptibility to oxidation and the relatively high surface roughness between conductive networks limit their further applications.

[0004] Graphene oxide has attracted much attention in the field of transparent conductive films due to its unique two-dimensional sheet structure and excellent film-forming properties. It can act as a physical barrier to isolate oxygen and moisture in the air, thereby improving the material's oxidation resistance. However, the surface of graphene oxide contains a large number of active groups such as carboxyl or hydroxyl groups, which are prone to self-deoxygenation, causing the graphene sheets to warp and thus destroying the conductive pathways of the film.

[0005] Therefore, there is an urgent need for a silver nanowire-graphene oxide-based conductive film with high light transmittance to solve the above problems. Summary of the Invention

[0006] Therefore, this invention provides a layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires, its preparation method, and its application, to solve the problem of decreased film conductivity caused by the easy oxidation of silver nanowires and the easy destruction of the conductive pathways of graphene oxide in the prior art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a layered transparent conductive film based on graphene oxide doped silver nanoparticles / silver nanowires is provided, wherein the film comprises, from bottom to top, a substrate layer, a conductive hydrophilic adhesive layer, a conductive layer and a functional layer.

[0008] Furthermore, the substrate layer is made of polyethylene terephthalate with a thickness of 150-200 μm, the conductive hydrophilic adhesive layer is made of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate), the conductive layer is made of silver nanowires, and the functional layer is made of graphene oxide sheets with in-situ grown silver nanoparticles.

[0009] According to a second aspect of the present invention, a method for preparing a layered transparent conductive thin film based on graphene oxide-doped silver nanoparticles / silver nanowires is provided, for preparing the aforementioned thin film, specifically comprising the following steps: S1. Preparation of silver nanowire dispersion: Polyvinylpyrrolidone was dissolved in ethylene glycol, and silver nitrate, sodium chloride, and sodium bromide were added. After dissolution, the mixture was stirred at 800 rpm for 5-15 min. The solution was then transferred to an oil bath and stirred at 800 rpm for 10 min at 160-180℃. The stirring was then turned off, and the mixture was kept at this temperature and allowed to stand for 60-90 min. After standing, the mixture was rapidly cooled to room temperature, centrifuged, and the precipitate was washed successively with deionized water, acetone, and ethanol before being dispersed in deionized water to obtain a silver nanowire dispersion. S2. Preparation of silver nanoparticle-doped graphene oxide solution: A solution A was prepared by adding a dispersion of silver nitrate and graphene oxide to deionized water and stirring until homogeneous. Tannic acid and sodium citrate were added to the deionized water and stirred until homogeneous, resulting in a solution denoted as solution B. Solutions A and B were heated separately. Solution B was then rapidly added to solution A, with a volume ratio of 3.2:1. The mixture was stirred for 5-15 minutes to obtain a mixed solution. The mixed solution was then transferred to an oil bath at 90-110°C and reacted for 10-30 minutes. After the reaction, the mixture was allowed to cool naturally to room temperature and washed with ethanol and water by centrifugation. Finally, the product was dispersed in water to obtain a silver nanoparticle-doped graphene oxide solution. Preparation of S3, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution: Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) was dissolved in deionized water to a final concentration of 3-4 g / L to obtain a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution. S4. Preparation of a bilayer silver nanowire-based transparent conductive film: After cleaning the polyethylene terephthalate substrate, a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution, a silver nanowire dispersion, and a silver nanoparticle-doped graphene oxide solution are sequentially coated onto it. Each coating is allowed to dry completely before the next layer is applied. The coating method is spin coating, the coating rate is 4000 rpm, and the drying conditions are drying at 120℃ for 10 min. The number of coating layers of the silver nanowire dispersion is 1-6 layers, and the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 1-5 layers.

[0010] Further, in step S1, the volume-to-mass ratio of ethylene glycol, polyvinylpyrrolidone, silver nitrate, sodium chloride, and sodium bromide is 100 mL: 0.66 g: 0.75 g: 2.57 mg: 1.11 mg; the polyvinylpyrrolidone has a molecular weight of 1,300,000 Da; the centrifugation conditions are 3000 rpm for 5 min; and the concentration of the silver nanowire dispersion is 3 mg / mL.

[0011] Furthermore, in the preparation of solution A in step S2, the mass-to-volume ratio of silver nitrate, graphene oxide dispersion, and water is 1 mg: 2 mL: 8 mL, the stirring time is 10 min, the stirring rate is 800 rpm, the heating temperature is 30 °C, and the concentration of graphene oxide dispersion is 3 mg / mL.

[0012] Further, in the preparation of solution B in step S2, the volume-to-mass ratio of deionized water, tannic acid, and sodium citrate is 1 mL: 1.2 mg: 1.8 mg, the stirring time is 20 min, the stirring rate is 800 rpm, the heating temperature is 30 °C, the oil bath temperature of the mixed solution is 100 °C, the reaction time is 20 min, and the concentration of the silver nanoparticle-doped graphene oxide solution is 4 mg / mL.

[0013] According to a third aspect of the present invention, an application of a layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires in the fabrication of OLED devices is provided.

[0014] Furthermore, the fabrication of OLED devices specifically includes the following steps: A layered transparent conductive film doped with silver nanoparticles / silver nanowires was placed in a vacuum evaporation chamber, and molybdenum trioxide was deposited under reduced pressure. After deposition, the film was removed and coated with a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30. After drying, the film was placed back in the vacuum evaporation chamber to deposit organic and inorganic layers sequentially, thus obtaining an OLED device.

[0015] Furthermore, the pressure reduction condition is pressure ≤ 7 × 10⁻⁶. -4 Pa; the deposition rate of the molybdenum trioxide is 0.2 Å / s, and the deposition thickness is 10 nm; the concentration of FS-30 in the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30 is 1 vol.%, the concentration of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) is 1 wt.%, the coating method is spin coating, and the coating rate is 2000 rpm.

[0016] Further, the organic layer comprises, from bottom to top, an N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer, a tris(8-hydroxyquinoline)aluminum-coumarin layer, and a tris(8-hydroxyquinoline)aluminum layer, all with a deposition rate of 1 Å / s. The deposition thickness of the N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer is 25 nm. The deposition thickness of the tri(8-hydroxyquinoline acid) aluminum-coumarin layer is 35 nm; wherein, the mass ratio of tri(8-hydroxyquinoline acid) aluminum to coumarin 545T is 100:1; the deposition thickness of the tri(8-hydroxyquinoline acid) aluminum layer is 35 nm; the inorganic layer comprises, from bottom to top, a lithium fluoride layer and an aluminum layer; wherein, the deposition rate of the lithium fluoride layer is 0.1 Å / s and the deposition thickness is 1 nm; the deposition rate of the aluminum layer is 5 Å / s and the deposition thickness is 100 nm.

[0017] The present invention has the following advantages: This invention employs silver nanowires (AgNWs) as the primary conductive material and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as a conductive hydrophilic adhesive layer. Silver nanoparticles (AgNPs) are grown in situ on graphene oxide (GO) to form a silver nanoparticle-doped graphene oxide (GO-AgNPs) functional layer, thus fabricating a flexible, multifunctional composite transparent conductive film (TCFs). The conductive hydrophilic adhesive layer enhances the hydrophilicity of the polyethylene terephthalate (PET) substrate surface, thereby promoting the uniform deposition of silver nanowires. AgNWs provide current transport channels, acting as the conductive host. GO-AgNPs cover the voids in the silver nanowire conductive network, not only enhancing the film's conductivity but also reducing the resistance between nanowires and helping to isolate AgNWs from atmospheric oxygen and water molecules, significantly improving its environmental stability. Due to these superior properties, flexible organic light-emitting diode (OLED) devices fabricated using these TCFs exhibit excellent performance. These results demonstrate that the high-performance TCF constructed using this method has broad application prospects in flexible electronic devices. Attached Figure Description

[0018] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0019] The structures, proportions, sizes, etc. illustrated in this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed herein, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.

[0020] Figure 1 A flowchart illustrating the preparation process of a bilayer silver nanowire-based transparent conductive film provided by this invention; Figure 2 The silver nanowires provided by this invention include transmission electron microscopy (TEM) images, X-ray diffraction patterns, and length and diameter distribution diagrams at the 200 nm-50 μm scale; wherein, Figure 2 (a), (b), and (c) are transmission electron microscopy (TEM) images of silver nanowire films at scales of 50 μm, 200 nm, and 100 nm, respectively. Figure 2 (d) is the X-ray diffraction pattern of silver nanowires. Figure 2 (e) and Figure 2 (f) shows the distribution of the length and diameter of the silver nanowires; Figure 3 The diagram shows the mechanism characterization of silver nanoparticles doped with graphene oxide provided by this invention; wherein, Figure 3 (a-a4) and Figure 3 (b-b4) are the mechanism diagrams and corresponding transmission scanning electron microscope images of different doping stages, respectively; Figure 3 (c) is the X-ray diffraction pattern of graphene oxide and silver nanoparticle-doped graphene oxide; Figure 3 (d) is the absorption spectrum of graphene oxide and silver nanoparticle-doped graphene oxide; Figure 3 (e1-e3) are X-ray photoelectron spectra of graphene oxide and silver nanoparticle-doped graphene oxide. Figure 4 The present invention provides a transmission electron microscope (TEM) image and particle size distribution map of silver nanoparticles doped with graphene oxide at the 500 nm scale; wherein, Figure 4 (a) is a transmission scanning electron microscope image; Figure 4 (b) is the corresponding particle size distribution diagram; Figure 5 The images shown are scanning electron microscope (SEM) images at the 1 μm scale of the thin films prepared in Comparative Examples 3, 5, 7, and Examples 1-5, as well as a photograph of the thin film prepared in Example 3; wherein, Figure 5 (a)-(c) are scanning electron microscope images of Comparative Examples 3, 5 and 7, respectively. Figure 5 (d)-(h) are scanning electron microscope images of Examples 1-5, respectively. Figure 5(i) A photograph of the thin film prepared in Example 3; Figure 6 The thin films prepared in the various embodiments and comparative examples of this invention are shown in the following figures: sheet resistivity, transmission spectrum at 300-850 nm, sheet resistivity diagram, transmittance diagram under 550 nm wavelength illumination, and FoM value diagram; wherein... Figure 6 (a) and Figure 6 (d) are sheet resistivity diagrams of the thin films prepared in Comparative Examples 1-6, Comparative Example 5, and Examples 1-5, respectively. Figure 6 (b) and Figure 6 (e) Transmittance diagrams of the films prepared in Comparative Examples 1-6, Comparative Example 5 and Examples 1-5 at 300-850 nm, respectively; Figure 6 (c) and Figure 6 (f) Sheet resistivity and FoM value of the thin films prepared in Comparative Examples 1-6, Comparative Examples 5 and Examples 1-5 at a wavelength of 550 nm; Figure 7 The images show the TCF (transformer charge distribution) of the films prepared in Examples 3, 5, and 7 of this invention, as well as the bending cycle test images, peeling cycle test images, and acid-base-salt corrosion resistance test images of the ITO-PET films. Additionally, the images show scanning electron microscope (SEM) images and corresponding resistivity changes of the films prepared in Comparative Examples 5, 7, and 3 after 50 days of exposure to air. Figure 7 (a) is a diagram of the bending cycle test of TCF. Figure 7 (b) is a diagram of the TCF peeling cycle test. Figure 7 (c) is a diagram of acid, alkali, and salt corrosion resistance test. Figure 7 (d) shows the resistance change curve of the thin film after 50 days of exposure to air. Figure 7 (e)-(g) are scanning electron microscope images at the 1 μm scale of the films prepared in Comparative Example 5, Comparative Example 7 and Example 3 after being exposed to air for 50 days; Figure 8 The following are the steady-state temperature curves, cyclic heating curves at 2V, infrared images of the TCF heated to its highest temperature at 0-2.5V, and electrothermal step temperature curves at 0.5-2.5V prepared in Example 3 of this invention; wherein, Figure 8 (a) is the steady-state temperature curve of TCF under voltages of 0.5-2.5V. Figure 8 (b) shows the cyclic heating curve of TCF at 2V. Figure 8 (c) is an infrared image of the TCF. Figure 8 (d) is the electric heating step temperature curve of TCF; Figure 9The X-band EMI absorption shielding effectiveness, reflection shielding effectiveness, shielding performance, average power coefficient, average total shielding effectiveness, and EMI mechanism diagrams of the thin films prepared in Comparative Examples 1, 3, 5, 7, and 3 are shown below; Figure 9 (a) shows the X-band absorption shielding effectiveness of the thin film. Figure 9 (b) is a diagram showing the effectiveness of reflection shielding. Figure 9 (c) is the overall shielding effectiveness diagram. Figure 9 (d) is the average power coefficient diagram. Figure 9 (e) represents the average total shielding effectiveness. Figure 9 (f) is a diagram of the X-band EMI mechanism in Example 3; Figure 10 The figures provided are the voltage-current density curves, voltage-brightness curves, voltage-current efficiency curves, voltage-power efficiency curves, voltage-external quantum efficiency curves, and normalized electroluminescence spectra in the OLED devices prepared based on the thin films of Example 6 and Comparative Example 7 of this invention; wherein, Figure 10 (a) is a voltage-current density curve of the OLED device. Figure 10 (b) is the voltage-brightness curve. Figure 10 (c) is a voltage-current efficiency curve of the OLED device. Figure 10 (d) is the voltage-power efficiency curve. Figure 10 (e) is the voltage-external quantum efficiency curve. Figure 10 (f) is the normalized electroluminescence spectrum of the OLED device prepared in Example 6. Detailed Implementation

[0021] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] According to a first aspect of the present invention, a layered transparent conductive film based on graphene oxide doped silver nanoparticles / silver nanowires is provided, wherein the film comprises, from bottom to top, a substrate layer, a conductive hydrophilic adhesive layer, a conductive layer and a functional layer.

[0023] The substrate layer is made of polyethylene terephthalate with a thickness of 150-200 μm; the conductive and hydrophilic adhesive layer is made of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate); the conductive layer is made of silver nanowires; and the functional layer is made of graphene oxide sheets with in-situ grown silver nanoparticles.

[0024] According to a second aspect of the present invention, a method for preparing a layered transparent conductive thin film based on graphene oxide-doped silver nanoparticles / silver nanowires is provided, for preparing the aforementioned thin film, specifically comprising the following steps: S1. Preparation of silver nanowire dispersion: Polyvinylpyrrolidone was dissolved in ethylene glycol, and silver nitrate, sodium chloride, and sodium bromide were added. After dissolution, the mixture was stirred at 800 rpm for 5-15 min. The solution was then transferred to an oil bath and stirred at 800 rpm for 10 min at 160-180℃. The stirring was then turned off, and the mixture was kept at this temperature and allowed to stand for 60-90 min. After standing, the mixture was rapidly cooled to room temperature, centrifuged, and the precipitate was washed successively with deionized water, acetone, and ethanol before being dispersed in deionized water to obtain a silver nanowire dispersion. S2. Preparation of silver nanoparticle-doped graphene oxide solution: A solution A was prepared by adding a dispersion of silver nitrate and graphene oxide to deionized water and stirring until homogeneous. Tannic acid and sodium citrate were added to the deionized water and stirred until homogeneous, resulting in a solution denoted as solution B. Solutions A and B were heated separately. Solution B was then rapidly added to solution A, with a volume ratio of 3.2:1. The mixture was stirred for 5-15 minutes to obtain a mixed solution. The mixed solution was then transferred to an oil bath at 90-110°C and reacted for 10-30 minutes. After the reaction, the mixture was allowed to cool naturally to room temperature and washed with ethanol and water by centrifugation. Finally, the product was dispersed in water to obtain a silver nanoparticle-doped graphene oxide solution. Preparation of S3, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution: Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) was dissolved in deionized water to a final concentration of 3-4 g / L to obtain a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution. S4. Preparation of a bilayer silver nanowire-based transparent conductive film: After cleaning the polyethylene terephthalate substrate, a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution, a silver nanowire dispersion, and a silver nanoparticle-doped graphene oxide solution are sequentially coated onto it. Each coating is allowed to dry completely before the next layer is applied. All coating methods were spin coating, with a coating rate of 4000 rpm and drying conditions of 120℃ for 10 min. The number of coating layers for the silver nanowire dispersion was 1-6 layers, and the number of coating layers for the silver nanoparticle-doped graphene oxide solution was 1-5 layers.

[0025] In step S1, the volume-to-mass ratio of ethylene glycol, polyvinylpyrrolidone, silver nitrate, sodium chloride, and sodium bromide is 100 mL: 0.66 g: 0.75 g: 2.57 mg: 1.11 mg; the polyvinylpyrrolidone has a molecular weight of 1,300,000 Da; the centrifugation conditions are 3000 rpm for 5 min; and the concentration of the silver nanowire dispersion is 3 mg / mL.

[0026] In step S2, during the preparation of solution A, the mass-to-volume ratio of silver nitrate, graphene oxide dispersion, and water is 1 mg: 2 mL: 8 mL, the stirring time is 10 min, the stirring rate is 800 rpm, the heating temperature is 30 °C, and the concentration of the graphene oxide dispersion is 3 mg / mL.

[0027] In step S2, the volume-to-mass ratio of deionized water, tannic acid, and sodium citrate is 1 mL: 1.2 mg: 1.8 mg. The stirring time is 20 min, the stirring speed is 800 rpm, the heating temperature is 30 °C, the oil bath temperature of the mixed solution is 100 °C, the reaction time is 20 min, and the concentration of the silver nanoparticle-doped graphene oxide solution is 4 mg / mL.

[0028] According to a third aspect of the present invention, an application of a layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires in the fabrication of OLED devices is provided.

[0029] The fabrication of OLED devices specifically includes the following steps: A layered transparent conductive film doped with silver nanoparticles / silver nanowires was placed in a vacuum evaporation chamber, and molybdenum trioxide was deposited under reduced pressure. After deposition, the film was removed and coated with a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30. After drying, the film was placed back in the vacuum evaporation chamber to deposit organic and inorganic layers sequentially, thus obtaining an OLED device.

[0030] The pressure reduction condition is that the pressure is ≤7×10. -4 Pa; the deposition rate of molybdenum trioxide was 0.2 Å / s, and the deposition thickness was 10 nm; the concentration of FS-30 in the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30 was 1 vol.%, the concentration of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) was 1 wt.%, the coating method was spin coating, and the coating rate was 2000 rpm.

[0031] The organic layer, from bottom to top, comprises an N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer, a tris(8-hydroxyquinoline)aluminum-coumarin layer, and a tris(8-hydroxyquinoline)aluminum layer, all deposited at a rate of 1 Å / s. The N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer has a deposition thickness of 25 nm. The deposition thickness of the tri(8-hydroxyquinoline acid) aluminum-coumarin layer is 35 nm; wherein, the mass ratio of tri(8-hydroxyquinoline acid) aluminum to coumarin 545T is 100:1; the deposition thickness of the tri(8-hydroxyquinoline acid) aluminum layer is 35 nm; the inorganic layers from bottom to top include a lithium fluoride layer and an aluminum layer; wherein, the deposition rate of the lithium fluoride layer is 0.1 Å / s and the deposition thickness is 1 nm; the deposition rate of the aluminum layer is 5 Å / s and the deposition thickness is 100 nm.

[0032] To better illustrate the technical path of the present invention, the following embodiments and comparative examples are provided.

[0033] Example 1 S1. Preparation of silver nanowire dispersion: Add 0.66 g of polyvinylpyrrolidone (molecular weight 1300000 Da) to 100 mL of ethylene glycol and stir to dissolve. Then add 0.75 g of silver nitrate, 2.57 mg of sodium chloride, and 1.11 mg of sodium bromide. Stir to dissolve and continue stirring at 800 rpm for 10 min. Transfer the solution to an oil bath and stir at 170 °C at 800 rpm for 10 min. Turn off the stirring and let it stand for 70 min. After standing, quickly cool to room temperature, centrifuge at 3000 rpm for 5 min, and collect the precipitate. Wash it successively with deionized water, acetone, and ethanol, and then disperse it in deionized water to obtain a silver nanowire dispersion with a final concentration of 3 mg / mL. S2. Preparation of silver nanoparticle-doped graphene oxide solution: 10 mg of silver nitrate and 20 mL of graphene oxide dispersion (3 mg / mL) were added to 80 mL of deionized water, denoted as solution A. 30 mg of tannic acid and 45 mg of sodium citrate were added to 25 mL of deionized water, denoted as solution B. Solutions A and B were heated to 30 °C, and then solution B was rapidly added to solution A. The mixture was stirred at 800 rpm for 10 min. Subsequently, the mixed solution was transferred to a 100 °C oil bath and reacted for 20 min. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, washed by centrifugation with ethanol and water, and finally dispersed in water to obtain a silver nanoparticle-doped graphene oxide solution with a final concentration of 4 mg / mL. Preparation of S3, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution: Dissolve 3.7g of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) in 1L of deionized water to obtain a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution. S4. Preparation of a bilayer silver nanowire-based transparent conductive film: After cleaning a 175μm thick polyethylene terephthalate substrate, a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution, a silver nanowire dispersion, and a silver nanoparticle-doped graphene oxide solution were sequentially coated onto it. Each coating was allowed to dry completely before the next layer was applied. All coating methods were spin coating, with a coating rate of 4000 rpm and drying conditions of 120℃ for 10 min. The silver nanowire dispersion had 5 coating layers and the silver nanoparticle-doped graphene oxide solution had 1 coating layer, named G1.

[0034] The thin film preparation process provided in Example 1 of this invention is as follows: Figure 1 As shown, this invention uses clean PET sheets as the substrate material and spin-coates a PEDOT:PSS solution as the adhesive layer to improve the surface hydrophilicity of PET, which is beneficial for the adhesion of AgNWs. Subsequently, AgNWs and a silver nanoparticle-doped graphene oxide dispersion are spin-coated sequentially. The one-dimensional bridging structure of AgNWs provides numerous conductive paths for the film, but it also creates many voids, increasing the surface roughness of the film and hindering its application. The silver nanoparticle-doped graphene oxide solution can fill the voids formed by the bridging of AgNWs, not only enhancing the conductivity of the film but also effectively reducing the surface roughness of TCFs, while simultaneously isolating air and significantly enhancing the oxidation resistance of TCFs.

[0035] Example 2 This embodiment is based on Embodiment 1, except that the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 2. The other specific parameters are the same as in Embodiment 1, and it is named G2.

[0036] Example 3 This embodiment is based on Embodiment 1, except that the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 3. The other specific parameters are the same as in Embodiment 1, and it is named G3.

[0037] Example 4 This embodiment is based on Embodiment 1, except that the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 4, while the other specific parameters are the same as in Embodiment 1, and it is named G4.

[0038] Example 5 This embodiment is based on Embodiment 1, except that the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 5, while the other specific parameters are the same as in Embodiment 1, and it is named G5.

[0039] Example 6 The transparent conductive film prepared in Example 3 was placed in a vacuum evaporation chamber and subjected to 7 × 10⁻⁶ evaporation conditions. -4 Molybdenum trioxide was deposited under reduced pressure at Pa. After deposition, the film was removed and coated with a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30. After drying at 120°C for 10 min, the film was placed back into the vacuum evaporation chamber to deposit organic and inorganic layers sequentially, thus obtaining an OLED device. The deposition rate of molybdenum trioxide was 0.2 Å / s, and the deposition thickness was 10 nm. The concentration of FS-30 in the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30 was 1 vol.%, the concentration of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) was 1 wt.%, the coating method was spin coating, and the coating rate was 2000 rpm. The organic layer, from bottom to top, comprises an N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer, a tris(8-hydroxyquinoline)aluminum-coumarin layer, and a tris(8-hydroxyquinoline)aluminum layer, all deposited at a rate of 1 Å / s. The N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer has a deposition thickness of 25 nm. The deposition thickness of the tri(8-hydroxyquinoline acid) aluminum-coumarin layer is 35 nm; wherein, the mass ratio of tri(8-hydroxyquinoline acid) aluminum to coumarin 545T is 100:1; the deposition thickness of the tri(8-hydroxyquinoline acid) aluminum layer is 35 nm; the inorganic layers from bottom to top include a lithium fluoride layer and an aluminum layer; wherein, the deposition rate of the lithium fluoride layer is 0.1 Å / s and the deposition thickness is 1 nm; the deposition rate of the aluminum layer is 5 Å / s and the deposition thickness is 100 nm.

[0040] Comparative Example 1 This comparative example is based on Example 3, except that the silver nanowire dispersion has only one coating layer, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. All other specific parameters are the same as in Example 3, and it is named A1.

[0041] Comparative Example 2 This comparative example is based on Comparative Example 1, except that the silver nanowire dispersion has two coating layers, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. The other specific parameters are the same as those in Comparative Example 1, and it is named A2.

[0042] Comparative Example 3 This comparative example is based on Comparative Example 1, except that the silver nanowire dispersion has 3 coating layers, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. The other specific parameters are the same as those in Comparative Example 1, and it is named A3.

[0043] Comparative Example 4 This comparative example is based on Comparative Example 1, except that the silver nanowire dispersion has 4 coating layers, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. All other specific parameters are the same as those in Comparative Example 1, and it is named A4.

[0044] Comparative Example 5 This comparative example is based on Comparative Example 1, except that the silver nanowire dispersion has 5 coating layers, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. The other specific parameters are the same as those in Comparative Example 1, and it is named A5.

[0045] Comparative Example 6 This comparative example is based on Comparative Example 1, except that the silver nanowire dispersion has 6 coating layers, no silver nanoparticle-doped graphene oxide solution is prepared, and no coating is performed. The other specific parameters are the same as those in Comparative Example 1, and it is named A6.

[0046] Comparative Example 7 This comparative example is based on Example 3, except that the number of coating layers of the silver nanowire dispersion is 5, no silver nanoparticle-doped graphene oxide solution is prepared and no coating is performed, and the graphene oxide solution is coated. The other specific parameters are the same as in Example 3, and it is named GO / A5.

[0047] In the embodiments and comparative examples provided by this invention, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), tris(8-hydroxyquinoline acid)aluminum (Alq3), N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine (NPB), and aluminum (Al) particles were all purchased from Xi'an Riyu Solar Energy Technology Co., Ltd.; lithium fluoride (LiF), coumarin 545T (C545T), molybdenum trioxide (MoO3), ethylene glycol (EG), and ethanol were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; polyvinylpyrrolidone (PVP, molecular weight 1,300,000) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; acetone was purchased from Tianjin Bohai Chemical Group Co., Ltd.; silver nitrate (AgNO3), sodium chloride (NaCl), and sodium bromide (NaBr) were purchased from Tianjin Kemai Chemical Co., Ltd. and Tianjin Jiangtian Chemical Technology Co., Ltd., respectively. Polyethylene terephthalate (PET, thickness: 175 μm) and FS-30 were purchased from Tianjin Wanhua Chemical Co., Ltd. and DuPont, USA, respectively. All materials were used without further processing. The graphene oxide dispersion was purchased from Suzhou CarbonFeng Graphene Technology Co., Ltd. (model XF020, concentration 1 mg / mL; after purchase, it was purified by centrifugation in our laboratory and then redispersed to 3 mg / mL).

[0048] Test Example 1 In this test example, silver nanowires were coated onto PET using the same coating method as in Example 1, with a coating thickness of one layer. The microstructure at different scales was observed using transmission electron microscopy to analyze the length and diameter distribution. Furthermore, the X-ray diffraction peaks of the silver nanowires were measured, and the results are as follows: Figure 2 As shown.

[0049] Depend on Figure 2 It can be seen that the AgNWs prepared by this invention are linear ( Figure 2 (a), (c) and (d)), and the diameter and length distribution are relatively uniform. Figure 2 (d) shows the typical face-centered cubic (FCC) structure of AgNWs, containing multiple distinct diffraction peaks corresponding to Ag(111), Ag(200), Ag(220), and Ag(311), respectively. The Ag(111) peak shows a significantly higher intensity than the others, indicating that the synthesized AgNWs are nanostructures with a high aspect ratio and preferentially grow along the Ag(111) direction. Furthermore, the absence of obvious impurity peaks in the spectrum demonstrates the high purity of the AgNWs. Dimensional statistical analysis reveals that the AgNWs have an average length of 88.3 μm, an average diameter of 74.7 nm, and an aspect ratio as high as 1182.

[0050] Test Example 2 This invention uses transmission electron microscopy to observe solutions of silver nanoparticles doped with graphene oxide at different stages, with observation times of 0 min, 5 min, 10 min, 15 min, and 20 min respectively. Then, X-ray diffraction, UV-Vis absorption spectroscopy, X-ray photoelectron spectroscopy, and particle size analysis were performed on the graphene oxide solution, the silver nanoparticle-doped graphene oxide solution, and the silver nanoparticle solution (purchased from Suzhou Xianfeng Nanomaterials Technology Co., Ltd., concentration 0.1 mg / mL), respectively. The results are as follows: Figure 3 and Figure 4 As shown.

[0051] Depend on Figure 3 (a-a4) shows that the preparation of silver nanoparticles doped with graphene oxide involved five stages within 0-20 min: the initial stage, absorption stage, reduction and growth stage, stabilization stage, and final product stage. The preparation mechanism is as follows: In the initial stage (0 min): silver ions in silver nitrate are uniformly dispersed in solution A containing graphene oxide sheets, and no AgNPs have yet formed. In the absorption stage (0-5 min), after tannic acid and sodium citrate are added to the mixed system as reducing and stabilizing agents, the oxygen-containing functional groups on the surface of the graphene oxide sheets preferentially adsorb silver ions from the solution onto the surface of the graphene oxide sheets, forming a silver ion-rich region, but no silver nanoparticles are yet generated. In the reduction and growth stage (5-10 min), tannic acid, rich in phenolic hydroxyl groups, acts as a reducing agent for silver ions. Silver ions adsorbed on the surface of graphene oxide sheets are reduced in situ to silver atoms, which then nucleate at defect sites or oxygen-containing functional groups on the graphene oxide sheet surface, gradually growing into silver nanoparticles. During the stabilization phase (10-15 min), the reduction rate of silver ions gradually slows down, the size and number of silver nanoparticles tend to stabilize, and their distribution on the graphene oxide sheets becomes more uniform. In the final stage (15-20 min), silver ions are essentially fully reduced, growing into silver nanoparticles uniformly distributed on the graphene oxide sheets with an average particle size of 57.6 nm. Figure 4 (b)).

[0052] Depend on Figure 3 (a-a4) and Figure 3 (b-b4) shows that as the reaction time increases, the diameter and number of silver nanoparticles on the graphene oxide sheets gradually increase. Figure 3 (c, d) show that silver nanoparticles were successfully doped onto the GO sheets, rather than being a simple physical mixture. Figure 3 (e1-e3) shows the X-ray photoelectron spectra of the three dispersions. Analysis of the characteristic peaks of C1s, O1s, and Ag3d confirms the results above. In summary, silver nanoparticles have been successfully doped at the nanoscale on GO sheets. Figure 4(a) The uniformity of silver nanoparticles doped with graphene oxide was measured by transmission electron microscopy at a scale of 500 nm. It can be clearly seen that the doping is relatively uniform. Figure 4 (b) The size of the silver nanoparticles was statistically analyzed, and it can be seen that the average diameter of the silver nanoparticles is 57.6 nm.

[0053] Test Example 3 This invention uses cold field emission scanning electron microscopy to observe the microstructure of the thin films prepared in Comparative Examples 3, 5, and 7, and Examples 1-5, and takes photographs of the thin film of Example 3. The results are as follows: Figure 5 As shown.

[0054] Depend on Figure 5 (a) and Figure 5 (b) It can be seen that as the number of silver nanowire spin coatings increases, the conductive network gradually becomes denser. Figure 5 (c) shows the structure of the AgNWs / GO film after spin-coating a graphene oxide dispersion onto silver nanowires. It can be seen that the uniform graphene oxide layer formed by coating effectively protects the silver nanowire network. Figure 5 Images (d)-(h) show scanning electron microscopy (SEM) images of the AgNWs / GO-AgNPs structures after coating with 1-5 layers of silver nanoparticle-doped graphene oxide solution. The results show that the number and density of AgNPs gradually increase with increasing GO-AgNPs content. Samples G1 and G2 have fewer and sparsely dispersed AgNPs on their surfaces, and the AgNWs network framework is clearly visible. Sample G3 exhibits a significantly increased AgNP density, with uniform particle size and excellent dispersion, achieving uniform modification of the AgNWs network and representing the sample with the best morphology. However, samples G4 and G5 show a further increase in the number of AgNPs on their surfaces, leading to localized particle stacking and aggregation. Furthermore, excessively high particle density reduces the film transmittance. Figure 5 (i) A photograph of the actual product of Example 3 is shown. It can be clearly observed that the film is uniformly transparent and has no obvious defects.

[0055] Test Example 4 This invention uses a UV-Vis spectrophotometer and a four-point probe system to measure the transmission spectra, transmittance, and sheet resistivity of the thin films prepared in each embodiment and comparative example, calculates the FoM value, and records the results. Figure 6 .

[0056] The FoM value is calculated using the following formula: Obtain; among them, T Represents light transmittance (550nm). Z 0 represents the free-space impedance, with a value of 377Ω. R S For surface resistance, σDC Let σ be the conductivity. OP The ratio of light conductivity to light transmittance is the largest; the larger the ratio, the better the conductivity and light transmittance of the thin film.

[0057] like Figure 6 As shown in (a)-(c), the optical transmittance and sheet resistivity of samples A1-A6 were tested in this invention. The results show that as the number of AgNWs spin-coated layers increases, the optical transmittance of the film gradually decreases, while the conductivity increases. Among them, sample A5 exhibits the best photoelectric performance, with an optical transmittance of 80.4% at 550 nm, a sheet resistivity of 4.22 Ω / sq, and a high FOM value of 387.

[0058] like Figure 6 As shown in (d)-(f), when the number of spin-coating cycles of GO-AgNPs is low, the functional layer gradually reduces the transmittance of the film while increasing its conductivity, resulting in a higher FOM value. When the coating amount is high, both the transmittance and conductivity of the film decrease simultaneously, leading to a lower FOM value. Therefore, considering all photoelectric properties, sample G3 exhibits the best performance. At this point, its optical transmittance at 550 nm is 78.6%, its sheet resistance is 2.98 Ω / sq, and its FOM value is as high as 494.

[0059] The above results indicate that adding a GO-AgNPs functional layer within a certain range can significantly improve the conductivity of the thin film, making TCF more suitable for transparent device applications and enhancing its antioxidant properties.

[0060] Test Example 5 To verify the stability of the films prepared in this invention, the films prepared in Comparative Examples 5, 7, and 3 were stored in an air environment with natural day-night light circulation for 50 days. The surface morphology at the 1 μm scale was observed using a cold field emission scanning electron microscope, and the resistance change curves over storage time were tested using a four-point probe system. Their cyclic bending and cyclic peeling capabilities were measured using a universal testing machine, with a bending radius of 1 mm for the bending performance test. The resistance changes of the three films after immersion in hydrochloric acid, sodium hydroxide, and sodium chloride solutions were evaluated to assess their resistance to acid, alkali, and salt solutions. The results were recorded. Figure 7 In addition, the present invention uses ITO-PET film (purchased from Kunming Wajin E-commerce Co., Ltd., 8-10Ω / sq) as a control group.

[0061] Figure 7The results in (a) show that the sheet resistivity of the ITO-PET film increases sharply and fails after 500 cycles. In contrast, although the sheet resistivity of the A5 film increases by about 10,000 times after 5,000 bends, the rate of increase is significantly lower than that of the ITO-PET film, and no failure is observed after 5,000 bends. The sheet resistivity of the GO / A5 film increases to 2,000 times its initial value after 5,000 bends, while the sheet resistivity of the G3 film increases by only 9.6 times. These results indicate that the G3 film has significantly better bending resistance than the ITO-PET film and has potential for application in flexible electronic devices.

[0062] Adhesion is another key requirement for TCF. Peel test results show that ( Figure 7 (b) The exposed AgNW network exhibits weak adhesion, with its resistance increasing significantly after only 10 test cycles, by approximately 3000 times. The GO / A5 sample, due to the uniform coverage of the AgNW network's gap structure by the GO layer and its tight adhesion to the substrate surface, performs better than the A5 sample. Its sheet resistance only gradually increases after 40 adhesion cycles, and increases by approximately 600 times after 100 adhesion cycles. However, by introducing a GO-AgNPs functional layer, AgNWs are effectively anchored, thereby enhancing interfacial adhesion; no significant increase in sheet resistance was observed after 100 adhesion cycles. Compared to pure GO, the uniformly doped AgNPs on the surface of the GO-AgNPs functional layer act as a conductive bridge between the AgNW network and the GO layer, significantly improving the continuity of the conductive network and enhancing conductivity. Due to the structure of the GO-AgNPs functional layer, the resistance change of the G3 sample after multiple adhesion tests is almost negligible.

[0063] The corrosion resistance of electronic devices is a key indicator for evaluating their stability. Corrosion resistance testing mainly includes aging tests under natural environments and acid-base-salt corrosion tests. First, to quantitatively assess the electrochemical stability of conductive films in different corrosive media, the films were immersed in 1 wt.% HCl, NaOH, and NaCl standard solutions for 10 minutes each, and then subjected to acid-base-salt corrosion tests. Figure 7 As shown in (c), the stability of sample G3 in all three corrosive media was significantly better than that of samples A5 and GO / A5. The effect was most pronounced in salt solutions. In NaCl solution, AgNWs underwent severe pitting corrosion and AgCl precipitation. - As a typical corrosive ion, it induces localized corrosion (pitting) of silver. This not only reduces the conductive path, but the resulting AgCl precipitate also adheres further to the AgNWs surface, hindering charge transport and leading to a significant increase in surface resistivity.

[0064] Furthermore, this invention also places three samples simultaneously in a natural atmospheric environment for aging tests. When AgNW comes into contact with air, it oxidizes and becomes an insulator. Figure 7 As shown in (d), the conductivity of the films decreased to varying degrees. Notably, the G3 sample, due to its GO-AgNPs functional layer, effectively blocked oxygen corrosion of the AgNWs network, maintaining a stable sheet resistivity. The sheet resistivity of the A5 film, however, increased significantly by approximately 40 times. Figure 7 (e)-(g) show the surface morphology changes of these three samples after 50 days of aging. The GO-AgNPs functional layer, acting as a physical barrier for the AgNWs network, not only enhances mechanical properties but also effectively isolates the AgNWs from external environmental corrosion. This result demonstrates that the GO-AgNPs functional layer plays a crucial role in improving the antioxidant properties of TCF.

[0065] Test Example 6 This invention uses a K-type thermocouple connected to a data acquisition multimeter to measure the temperature change and cycle stability of the thin film prepared in Example 3 during the electric heating process. The results are recorded in [the relevant documentation]. Figure 8 The film used in the electric heating test was 3 cm long and 1.5 cm wide.

[0066] like Figure 8 As shown in (a), the temperature of the thin film prepared in Example 3 of the present invention exhibits a positive correlation with the voltage, and reaches its highest temperature of 109°C at a voltage of 2.5V. In addition, the thin film has excellent temperature rise response performance, reaching steady-state temperature within 70s at voltages ranging from 0 to 2.5V.

[0067] This invention measures the cyclic curve of the thin film repeatedly heated to its maximum temperature at 2.5V to verify its temperature reproducibility. Figure 8 (b) It can be seen that the stable temperature change of the film fluctuates little, indicating that the film has good stability when heated by electricity. In order to verify the uniform heating of the film under different voltages, the present invention took infrared images of the film heated to the highest temperature under a voltage of 0-2.5V ( Figure 8 (c)). It can be seen that the highest temperatures of the thin film under 0-2.5V voltages are 35.5℃, 48.5℃, 65.1℃, 84.3℃, and 109℃, respectively, which are consistent with... Figure 8 Corresponding to the result in (a), the heating region is stable with minimal fluctuations, indicating that the thin film exhibits good stability during electrical heating. This invention allows the thin film to undergo different temperature gradients by continuously adjusting the voltage. Figure 8 (d) It can be seen that the temperature during the depressurization process is slightly higher than that during the pressurization process. This is because the heat accumulated during the pressurization process is not dissipated in time, which is normal in step tests.

[0068] Test Example 7 To verify the effect of the number of silver nanowire coating layers on the electromagnetic interference (EMI) shielding effectiveness of the intact thin film, samples A1, A3, A5, GO / A5, and G3 were tested. The EMI shielding effectiveness (SE) and light transmittance of TCFs were evaluated in the X-band (8.2-12.4 GHz) using the waveguide method combined with a vector network analyzer. The results are recorded in [the relevant documentation]. Figure 9 .

[0069] Depend on Figure 9 It can be seen that as the amount of AgNWs increases, the average total shielding effectiveness (SE) of sample A5 decreases. T ), absorption and shielding effectiveness (SE) A ) and reflection shielding effectiveness (SE) R All of them have been improved to varying degrees. For example, Figure 9 As shown in (ac), SE of A5 T The electromagnetic interference shielding capability of the G3 sample reached 21 dB, while the presence of the GO-AgNPs functional layer further enhanced its electromagnetic shielding capability, resulting in a higher SE. T It reached 27 dB. For example... Figure 9 As shown in (d) and (e), by comprehensively calculating the proportions of R, T, and A for each of the five samples, as well as the average electromagnetic shielding performance, it was found that R accounts for the largest proportion, and gradually increases with the increase of AgNWs dosage and film conductivity. This indicates that the electromagnetic shielding capability of the film is mainly provided by the reflection mechanism of the AgNWs network. The interaction between the incident electromagnetic wave and the G3 sample generates multiple loss mechanisms, which together determine the EMI SE (Electromagnetic Shielding Performance) of the film. Figure 9 (f) The main loss types of thin films for incident electromagnetic waves include ohmic loss, multiple reflection loss, impedance mismatch, and polarization loss. Ohmic loss mainly originates from the AgNWs network and the conductive paths formed by AgNPs in GO. Multiple reflection loss occurs at the air / thin film interface, the interface between GO-AgNPs and AgNWs, and within the AgNWs network. Impedance mismatch occurs at the air / thin film interface, causing initial reflection of the incident electromagnetic wave and preventing it from entering the thin film. Polarization loss is mainly contributed by the dipole polarization of oxygen-containing functional groups in the GO layer and the interfacial polarization caused by interfacial charge accumulation. The synergistic effect of these mechanisms enables the thin film to effectively absorb and reflect electromagnetic waves, thus providing excellent electromagnetic shielding performance.

[0070] Test Example 8 This invention systematically evaluated the electroluminescence performance of the OLED device prepared in Example 6 using an OLED photoelectric measurement system (purchased from Suzhou Fushida Scientific Instruments Co., Ltd.); and used the same preparation method to prepare an OLED device for Comparative Example 7 as a control group. The results were recorded in [document name missing]. Figure 10 .

[0071] The performance of OLED devices, such as Figure 10 As shown. By Figure 10 As can be seen from (a) and (b), the maximum luminance (Lmax) of the device reaches 10000 cd / m². 2 The corresponding voltage is 8V, and the current density at this time is 98.4mA / cm². 2 . Figure 10 (c)-(e) illustrate the relationship between the device's current efficiency (CE), power efficiency (PE), and external quantum efficiency (EQE) and voltage. It can be seen that in Example 6, the maximum CE occurs at 7.0V, reaching 12.4 cd / A; the maximum PE occurs at 6.5V, reaching 5.61 lm / W; and the maximum EQE also occurs at 7.0V, reaching 3.7%. The following relationships satisfy the relationships between PE, CE, voltage, luminance, and current density: ; ; Where B is luminance and J is current density, in mA / cm². 2 U represents voltage, measured in volts (V). PE is significantly affected by voltage; therefore, as voltage increases, PE will inevitably decrease.

[0072] also, Figure 10 The results show that the current density of the GO / A5 sample is higher than that of the G3 sample, but its brightness, current efficiency, power efficiency, and external quantum efficiency are all significantly lower than those of the G3 sample. This is because GO has a high intrinsic resistance, and the current paths in the AgNWs network and GO layer mainly rely on the non-defective parts of GO. This non-uniform electric field distribution leads to abnormal current concentration, resulting in a large amount of ineffective current through short-circuit channels. The increase in current density is not due to increased effective carrier injection, but rather the presence of leakage current paths. The addition of AgNPs in the GO-AgNPs functional layer can act as a bridge connecting the GO layer and the AgNWs network, allowing for smoother carrier passage. The homogenization of the electric field reduces local short-circuit channels, thereby reducing the overall current density. Therefore, the current density of the G3 sample is lower than that of the GO / A5 sample, but its brightness and current efficiency are much higher. At 8V, the maximum brightness (Lmax) of the G3 sample reaches 10000 cd / m². 2 The current efficiency at this point is three times that of the GO / A5 sample. Figure 10 The results in (f) show that the peak position of the emission spectrum does not change significantly with voltage. This indicates that the emission region of the OLED device is stable and does not change with voltage, thus exhibiting stable electroluminescence performance.

[0073] Summarize: This invention prepares flexible TCFs with a structure of PEDOT:PSS / AgNWs / GO-AgNPs. This film exhibits excellent conductivity and light transmittance, as well as bend resistance, oxidation resistance, low surface roughness, and strong adhesion to substrates. Electrothermal devices based on this TCF can reach a temperature of 109°C at 2.5V and maintain stability over a long period. Furthermore, thanks to the excellent conductivity of AgNWs and the high impedance mismatch with air, the TCFs exhibit excellent EMI SE. The G3 film achieves an EMI SE of 27dB at 80.4% transmittance, meeting the requirements for commercial applications. OLED devices prepared with the G3 film demonstrate excellent electroluminescence performance. (Lmax, CE) max PE max and EQE max Reaching 10000 cd / m 2 With a current efficiency of 12.4 cd / A, 5.61 lm / W, and 3.7%, its current efficiency at maximum brightness is three times that of the GO / A5 sample, indicating that this TCF has broad application prospects in the field of flexible electronic devices.

[0074] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires, characterized in that, The film comprises, from bottom to top, a substrate layer, a conductive hydrophilic adhesive layer, a conductive layer, and a functional layer.

2. The thin film as described in claim 1, characterized in that, The substrate layer is made of polyethylene terephthalate with a thickness of 150-200 μm; the conductive hydrophilic adhesive layer is made of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate); the conductive layer is made of silver nanowires; and the functional layer is made of graphene oxide sheets with in-situ grown silver nanoparticles.

3. A method for preparing a layered transparent conductive thin film based on graphene oxide-doped silver nanoparticles / silver nanowires, used to prepare the thin film according to any one of claims 1-2, characterized in that, Specifically, the following steps are included: S1. Preparation of silver nanowire dispersion: Polyvinylpyrrolidone was dissolved in ethylene glycol, and silver nitrate, sodium chloride, and sodium bromide were added. After dissolution, the mixture was stirred at 800 rpm for 5-15 min. The solution was then transferred to an oil bath and stirred at 800 rpm for 10 min at 160-180℃. The stirring was then turned off, and the mixture was kept at this temperature and allowed to stand for 60-90 min. After standing, the mixture was rapidly cooled to room temperature, centrifuged, and the precipitate was washed successively with deionized water, acetone, and ethanol before being dispersed in deionized water to obtain a silver nanowire dispersion. S2. Preparation of silver nanoparticle-doped graphene oxide solution: A dispersion of silver nitrate and graphene oxide was added to deionized water and stirred until homogeneous to obtain a solution, denoted as solution A. Add tannic acid and sodium citrate to deionized water and stir until homogeneous to obtain a solution, denoted as solution B; heat solutions A and B separately. Then, solution B was quickly added to solution A; the volume ratio of solution A to solution B was 3.2:1; the mixture was stirred for 5-15 min to obtain a mixed solution; subsequently, the mixed solution was transferred to an oil bath at 90-110℃ and reacted for 10-30 min; after the reaction was completed, the mixture was naturally cooled to room temperature and washed with ethanol and water by centrifugation; finally, the product was dispersed in water to obtain a silver nanoparticle-doped graphene oxide solution. Preparation of S3, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution: Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) was dissolved in deionized water to a final concentration of 3-4 g / L to obtain a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution. S4. Preparation of a bilayer silver nanowire-based transparent conductive film: After cleaning the polyethylene terephthalate substrate, a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution, a silver nanowire dispersion, and a silver nanoparticle-doped graphene oxide solution are sequentially coated onto it. Each coating is allowed to dry completely before the next layer is applied. The coating method is spin coating, the coating rate is 4000 rpm, and the drying conditions are drying at 120℃ for 10 min. The number of coating layers of the silver nanowire dispersion is 1-6 layers, and the number of coating layers of the silver nanoparticle-doped graphene oxide solution is 1-5 layers.

4. The preparation method according to claim 3, characterized in that, In step S1, the volume-to-mass ratio of ethylene glycol, polyvinylpyrrolidone, silver nitrate, sodium chloride, and sodium bromide is 100 mL: 0.66 g: 0.75 g: 2.57 mg: 1.11 mg; the polyvinylpyrrolidone has a molecular weight of 1,300,000 Da; the centrifugation conditions are 3000 rpm for 5 min; and the concentration of the silver nanowire dispersion is 3 mg / mL.

5. The preparation method according to claim 3, characterized in that, In the preparation of solution A in step S2, the mass-volume ratio of silver nitrate, graphene oxide dispersion and water is 1 mg: 2 mL: 8 mL, the stirring time is 10 min, the stirring rate is 800 rpm, the heating temperature is 30 °C, and the concentration of graphene oxide dispersion is 3 mg / mL.

6. The preparation method according to claim 3, characterized in that, In the preparation of solution B in step S2, the volume-to-mass ratio of deionized water, tannic acid, and sodium citrate is 1 mL: 1.2 mg: 1.8 mg; the stirring time is 20 min; the stirring speed is 800 rpm; the heating temperature is 30 °C; the oil bath temperature of the mixed solution is 100 °C; the reaction time is 20 min; and the concentration of the silver nanoparticle-doped graphene oxide solution is 4 mg / mL.

7. The application of a layered transparent conductive film based on graphene oxide-doped silver nanoparticles / silver nanowires in the fabrication of OLED devices, characterized in that, The conductive thin film is prepared using any one of claims 1-2.

8. The application as described in claim 7, characterized in that, The fabrication of OLED devices specifically includes the following steps: A layered transparent conductive film doped with silver nanoparticles / silver nanowires was placed in a vacuum evaporation chamber, and molybdenum trioxide was deposited under reduced pressure. After deposition, the film was removed and coated with a poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30. After drying, the film was placed back in the vacuum evaporation chamber to deposit organic and inorganic layers sequentially, thus obtaining an OLED device.

9. The application as described in claim 8, characterized in that, The pressure reduction condition is pressure ≤ 7 × 10⁻⁶. -4 Pa; the deposition rate of the molybdenum trioxide is 0.2 Å / s, and the deposition thickness is 10 nm; the concentration of FS-30 in the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) solution containing FS-30 is 1 vol.%, the concentration of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) is 1 wt.%, the coating method is spin coating, and the coating rate is 2000 rpm.

10. The application as described in claim 8, characterized in that, The organic layer, from bottom to top, comprises an N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer, a tris(8-hydroxyquinoline)aluminum-coumarin layer, and a tris(8-hydroxyquinoline)aluminum layer, all deposited at a rate of 1 Å / s. The N,N'-bis(1-naphthyl)-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine layer has a deposition thickness of 25 nm. The deposition thickness of the tri(8-hydroxyquinoline acid) aluminum-coumarin layer is 35 nm; wherein, the mass ratio of tri(8-hydroxyquinoline acid) aluminum to coumarin 545T is 100:1; the deposition thickness of the tri(8-hydroxyquinoline acid) aluminum layer is 35 nm; the inorganic layer comprises, from bottom to top, a lithium fluoride layer and an aluminum layer; wherein, the deposition rate of the lithium fluoride layer is 0.1 Å / s and the deposition thickness is 1 nm; the deposition rate of the aluminum layer is 5 Å / s and the deposition thickness is 100 nm.